2009
DOI: 10.1177/070674370905400302
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic Symptoms as a Continuum between Normality and Pathology

Abstract: It is possible that clinical phenomena associated with mental illness lie on a continuum with normality. Along these lines, several recent reports have studied the prevalence of hallucinations and other psychotic symptoms in the general population. A recent meta-analysis of risk factors to develop subclinical psychotic symptoms shows associations with male sex, migrant status, living in urban centres, developmental stage, psychoactive drug use, and child and adult social adversity, 1 all of which are risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 71 publications
0
52
0
3
Order By: Relevance
“…By finessing the pathological hallmarks of traditional psychotic phenomena, our research risks losing the essence of psychosis. If, as some have suggested (Stip & Letourneau, 2009), we need to look beyond old-fashioned psychotic symptoms for novel treatment targets, we need to ensure that our phenomenological skills have not atrophied to such an extent that we are unable to define and characterize these new entities.…”
Section: A Way Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…By finessing the pathological hallmarks of traditional psychotic phenomena, our research risks losing the essence of psychosis. If, as some have suggested (Stip & Letourneau, 2009), we need to look beyond old-fashioned psychotic symptoms for novel treatment targets, we need to ensure that our phenomenological skills have not atrophied to such an extent that we are unable to define and characterize these new entities.…”
Section: A Way Forwardmentioning
confidence: 99%
“…Since around the mid-1980s it has gained a large number of adherents so that it is now becoming the accepted dogma. Although the theory can call upon a relatively large body of evidence in its support, drawn from phenomenological studies, epidemiology, developmental psychopathology and cognitive psychology (Johns & van Os, 2001 ;Freeman, 2007 ;Stip & Letourneau, 2009 ;van Os et al 2009), there is also work that suggests that viewing all psychotic phenomena as continua may lead us down a blind alley in understanding the nature of psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Si la dissociation est bien à l'avant-plan des symptômes et que l'origine du trouble est traumatique, ne serait-il pas mieux de considérer que les symptômes psychotiques sont tout simplement une part de l'expérience de ces personnes, sans les considérer pathologiques en soi (Stip et Letourneau, 2009) ? En effet, de nombreuses études ont montré que les symptômes psychotiques, notamment les délires et les hallucinations, sont prévalents dans la population générale (Beck et Rector, 2003 ;Ohayon, 2000) et qu'ils sont associés à la sévérité et à la fréquence des traumatismes dans l'enfance (Shevlin et al, 2007 ;Shevlin et al, 2008).…”
Section: Discussionunclassified
“…Certains auteurs prônent déjà le traitement des différentes dimensions de la schizophrénie plutôt que le simple traitement des symptômes psychotiques (Stip et Letourneau, 2009 …”
Section: Discussionunclassified
“…The prevalence of subclinical psychotic symptoms and experiences in the general population is much higher than that of psychotic disorder, indicating that Introduction endorsing such experiences does not necessarily lead to need for care. Recent meta analyses have shown that subclinical psychotic experiences, such as hallucinatory experiences or delusional thinking, are reported by as many as 10 30% of the general population (Nuevo, Chatterji, Verdes, Naidoo, Arango & Ayuso Mateos, 2010;Stip & Letourneau, 2009). The dimensions underlying these symptoms have shown to be similar in both clinical and non clinical psychosis (the latter referring to schizotypy, the non clinical manifestation of psychosis at the level of personality structure) (Johns & van Os, 2001; Rossi & Daneluzzo, 2002;Vollema & Hoijtink, 2000).…”
Section: The Extended Psychosis Phenotypementioning
confidence: 99%